A companion to the Etruscans - Bell, Sinclair; Carpino, Alexandra Ann (Wiley-Blackwell, 2016)
Presents a selection of innovative scholarship on the Etruscans, a vibrant, independent people whose distinct civilization flourished in central Italy for most of the first millennium BCE and whose artistic, social and cultural traditions helped shape the ancient Mediterranean, European, and Classical worlds. The volume includes contributions from an international cast of established and emerging scholars, and offers perspectives on Etruscan art and culture, including analysis of the most up-to-date research and archaeological discoveries. The authors reassess and evaluate traditional topics like architecture, wall painting, ceramics, and sculpture as well as new ones such as textile archaeology, while also addressing themes that have yet to be thoroughly investigated in the scholarship, such as the obesus etruscus, the function and use of jewelry at different life stages, Greek and Roman topoi about the Etruscans, the Etruscans' reception of ponderation, and more. This volume counters the claim that the Etruscans were culturally inferior to the Greeks and Romans by emphasizing fields where the Etruscans were either technological or artistic pioneers and by reframing similarities in style and iconography as examples of Etruscan agency and reception rather than as a deficit of local creativity
Includes bibliographical references and index. - Print version record
Keywords: Electronic books; Geschichte; Kunst; Etrusker